Variability of structures in German intensive care units–a representative, nationwide analysis - Graf, Jürgen; Reinhold, Andrea; Brunkhorst, Frank M.; Ragaller, Max; Reinhart, Konrad; Löffler, Markus; Engel, Christoph (Wiener klinische Wochenschrift, 2010)
BACKGROUND Structures in intensive care medicine comprise human as well as material resources, organization, and management and may be related to processes thereby affecting patients’ outcomes. Utilizing a unique data base we evaluated structures of German intensive care units (ICUs). METHODS The study was carried out by the German Competence Network Sepsis (SepNet). Data were prospectively collected on a cross-sectional basis in a representative random sample of German hospitals utilizing a questionnaire. Structures were related to ICU outcome of patients with severe sepsis or septic shock. The sample was subdivided in 5 strata according to hospital size. RESULTS A total of 454 ICUs cared for 3877 patients including 415 patients (11%) with severe sepsis or septic shock. The mean number of beds per ICU was 10.4, the ratio of ICU to hospital beds 1:27, both with significant differences depending on hospital size. 81% of the ICUs provided around the clock physician presence (range: 66-98% across hospital strata, p < 0.001). Shift-wise, one nurse was responsible for a mean number of 2.7 patients (morning 1:2.3, afternoon 1:2.6, night 1:3.3 patients) with significant variation according to hospital size (smaller hospitals 1:2.9, university hospitals 1:2.1, p < 0.001). More than half of all German ICUs are lead by anesthesiologists. Neither physician nor nurse staffing was associated with mortality in the subset of patients with sepsis. CONCLUSIONS In a representative, nationwide sample of German ICUs key elements of structures varied considerably with respect to hospital size. This has to be considered when proposing standards, reimbursement strategies, or quality assessment.